2014
DOI: 10.1038/srep03743
|View full text |Cite
|
Sign up to set email alerts
|

Chemical signatures and new drug targets for gametocytocidal drug development

Abstract: Control of parasite transmission is critical for the eradication of malaria. However, most antimalarial drugs are not active against P. falciparum gametocytes, responsible for the spread of malaria. Consequently, patients can remain infectious for weeks after the clearance of asexual parasites and clinical symptoms. Here we report the identification of 27 potent gametocytocidal compounds (IC50 < 1 μM) from screening 5,215 known drugs and compounds. All these compounds were active against three strains of gamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
133
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(141 citation statements)
references
References 56 publications
7
133
1
Order By: Relevance
“…In this previous study, result mentioned the experimental verification of early stage gametocytocidal activity in the development of new antimalarial activity. These studies had confirmed that effects of tryptanthrin and the derivatives NT1, T8, epoxomicin and chloroquine were investigated on the development of stage II to stage V gametocytes [22]. Although marine algae have been recognized as attractive sources of known bioactive compounds, very little research has been focused on antiprotozoal activity.…”
Section: Discussionmentioning
confidence: 64%
“…In this previous study, result mentioned the experimental verification of early stage gametocytocidal activity in the development of new antimalarial activity. These studies had confirmed that effects of tryptanthrin and the derivatives NT1, T8, epoxomicin and chloroquine were investigated on the development of stage II to stage V gametocytes [22]. Although marine algae have been recognized as attractive sources of known bioactive compounds, very little research has been focused on antiprotozoal activity.…”
Section: Discussionmentioning
confidence: 64%
“…Primary hit rates (>80% inhibition at 5 μM) of 4.5-24% [20,23,27,29] were achieved when screened against stage IV/V gametocytes; this increased to 33% against stage I-III gametocytes [23,26]. Furthermore, although the rank-order of hits were similar, there was not complete overlap between MMV Malaria Box screens conducted with different assay platforms or between laboratories using the same assay platform [24,25].…”
Section: Transmission-blocking Compounds: Challenges To Successmentioning
confidence: 95%
“…The Medicines for Malaria Venture (MMV) Malaria Box of 400 compounds (selectively active against asexual parasites [22]) has been screened worldwide for activity against stage IV/V gametocytes [20,[23][24][25][26][27][28][29][30][31]. Primary hit rates (>80% inhibition at 5 μM) of 4.5-24% [20,23,27,29] were achieved when screened against stage IV/V gametocytes; this increased to 33% against stage I-III gametocytes [23,26].…”
Section: Transmission-blocking Compounds: Challenges To Successmentioning
confidence: 99%
See 2 more Smart Citations